PENERAPAN PENDEKATAN MODEL-ELICITING ACTIVITIES (MEAS) DALAM PEMBELAJARAN MATEMATIKA UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA SMP - Tresna Nur’aviandini; Yaya Sukjaya Kusumah; Bambang Avip Priatna (Integral : Pendidikan Matematika, 2018)
This study is motivated by the problem of student’s critical thinking skill. The purpose of this study are: 1) to investigate whether students who undertake mathematics learning with Model-Eliciting Activities (MEAs) approach have higher improvement in critical thinking skill compared to those who undertake learning with conventional; 2) to investigate students’ mathematical disposition towards mathematics learning under Model-Eliciting Activities (MEAs) approach. This study used quasi-experimental methods, while the population were all students of 8th grade of SMP Negeri 2 Cimahi, Academic Year 2012/2013. The test and non-test instruments were deployed in this study. The kind of test instruments used in this research was essay based on indicator of critical thinking skill and non-test instruments were in the forms of questionnaire, observation sheet, and students’ daily jounal. The results of this study show that: 1) students who undertake mathematics learning with Model-Eliciting Activities (MEAs) approach have higher improvement in critical thinking skill compared to those who undertake mathematics learning with conventional approach; 2) students’ enhancement on mathematical disposition towards mathematics learning under Model-Eliciting Activities (MEAs) approach is relatively good.Keyword: Critical thinking skill, Model-Eliciting Activities (MEAs) approach, mathematical disposition.